Advances in Experimental Medicine and Biology
DOI: 10.1007/0-387-24980-x_27
|View full text |Cite
|
Sign up to set email alerts
|

Quality Related Minimization of Acrylamide Formation - An Integrated Approach

Abstract: An integrated approach is described with respect to acrylamide minimization in heated foodstuffs. All relevant variables have to be considered and the main focus is on maintaining the expected product quality. The role of the processes at the interface between product and heating medium during processing is characterized for the case of frying operations. Examples of parameters influencing these processes with respect to minimizing acrylamide and maintaining product quality (e.g. brown color) are described. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 8 publications
2
17
0
Order By: Relevance
“…In contrast to the experiments with the potato model system (Mestdagh et al, 2007) and in accordance with previous reports (Franke et al, 2005;, NaCl significantly decreased the acrylamide content (Table 1). Moreover, at the highest concentration level, applied in the blanching water (0.1 M), the final salt content in the crisps (3.5 g kg À1 crisp) still appeared to be only half of the amount being present in salted crisps, sold in retail.…”
Section: Influence Of Additives In Blanching Water On Acrylamide Formsupporting
confidence: 92%
See 2 more Smart Citations
“…In contrast to the experiments with the potato model system (Mestdagh et al, 2007) and in accordance with previous reports (Franke et al, 2005;, NaCl significantly decreased the acrylamide content (Table 1). Moreover, at the highest concentration level, applied in the blanching water (0.1 M), the final salt content in the crisps (3.5 g kg À1 crisp) still appeared to be only half of the amount being present in salted crisps, sold in retail.…”
Section: Influence Of Additives In Blanching Water On Acrylamide Formsupporting
confidence: 92%
“…Also the addition of CaCl 2 , eventually in combination with calcium-L-lactate, did not significantly change the surface colour, compared to the control. Previously, it was also shown that addition of NaCl and CaCl 2 to potato strips did not change the surface colour upon subsequent frying (Bunger et al, 2003;Franke et al, 2005;Gö kmen & Senyuva, 2007), although other studies found a reduced browning upon addition of NaCl (Santis, Mendoza, Moyano, Pedreschi, & Dejmek, 2007;.…”
Section: Colour Evaluation Of Potato Crispsmentioning
confidence: 93%
See 1 more Smart Citation
“…These earlier reported experiments were however performed in an aqueous asparagine/glucose model system (Kolek, Simko, & Simon, 2006). Yet, in real foodstuffs, NaCl appeared to have more acrylamide lowering properties compared to model systems (Franke, Sell, & Reimerdes, 2005;Gökmen & Senyuva, 2007a), as investigated in a subsequent study (Mestdagh, De Wilde, Delporte, Van Peteghem, & De Meulenaer, 2007). In addition, the effect of sodium acid pyrophosphate (Na 2 H 2 P 2 O 7 ) was evaluated.…”
Section: Influence Of Additives On Acrylamide Formation In Potato Modmentioning
confidence: 98%
“…However those blanched in distilled water at 85°C, citric acid (0.05), L-cysteine (0.1M) had significantly the lowest values. Acidification may moreover result in a sour product taste (Kita et al, 2004;Franke et al, 2005). This effect however depends upon the applied soaking or blanching treatment and the type and concentration of the acid used.…”
Section: Effect Of Different Fresh Leaves Into Fryingmentioning
confidence: 99%